Subtract <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> from both sides of the equation.

Subtract <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> from <math><mstyle displaystyle="true"><mn>9</mn></mstyle></math> .

Divide each term in <math><mstyle displaystyle="true"><mn>2</mn><msup><mrow><mi>e</mi></mrow><mrow><mi>x</mi><mo>+</mo><mn>1</mn></mrow></msup><mo>=</mo><mn>8</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><msup><mrow><mi>e</mi></mrow><mrow><mi>x</mi><mo>+</mo><mn>1</mn></mrow></msup></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Divide <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Take the natural logarithm of both sides of the equation to remove the variable from the exponent.

Expand <math><mstyle displaystyle="true"><mi>ln</mi><mrow><mo>(</mo><msup><mrow><mi>e</mi></mrow><mrow><mi>x</mi><mo>+</mo><mn>1</mn></mrow></msup><mo>)</mo></mrow></mstyle></math> by moving <math><mstyle displaystyle="true"><mi>x</mi><mo>+</mo><mn>1</mn></mstyle></math> outside the logarithm.

The natural logarithm of <math><mstyle displaystyle="true"><mi>e</mi></mstyle></math> is <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi><mo>+</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> from both sides of the equation.

The result can be shown in multiple forms.

Exact Form:

Decimal Form:

Do you know how to Solve for x 1+2e^(x+1)=9? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.